CHANGE IN THE QUALITY OF DIESEL FUEL UNDER LONG-TERM STORAGE CONDITIONS - VOVK, YULIIA; MATVYEYEVA, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The results of research on changes in the physical and chemical quality indicators of diesel fuel, which was in long-term storage at petroleum product supply enterprises, are presented. The practical experience of operation has shown that sources of pollution can be: technological equipment and air with which the fuel is in contact, as well as products of the vital activity of microorganisms. It is shown that during the five-year storage period, changes in its quality did not exceed regulatory requirements. The dynamics of changes in fuel water content, the content of mechanical impurities, and the oxidizing and lubricating capacity of fuel have been established. Studies of fuel contamination have shown a fourfold increase (from 3.2 to 13 mg/kg) of the mass fraction of mechanical impurities in fuel when it is stored in storage tanks.The article presents experimental and practical data on changes in the oxidative stability of diesel fuel over a five-year storage period. The results indicate the constant action of physical and chemical processes in the fuel, which intensify the oxidation processes. This is confirmed by a 3.3-fold increase in the oxidation stability of the fuel.  An improvement in the lubricating ability of the fuel, a reduction in the wear of the friction pairs was revealed, which correlates with the relevant data on the increase in fuel oxidation products. The obtained scientific and practical results will be taken into account in the preparation of Recommendations on the technology of long-term storage of light petroleum products for petroleum product supply enterprises
Keywords: diesel fuel; physical and chemical properties; fuel and lubricants; storage; stability; oxidation; lubricating layer; wear; friction; rational use; ecological properties